Comparison of antibody-scTRAIL Fc fusion proteins with varying valency for EGFR and TRAIL receptors - Dennis Michler; Oliver Seifert; Klaus Pfizenmaier; Roland E. Kontermann (Scientific Reports)
Abstract Fusion proteins combining TNF-related apoptosis inducing ligand (TRAIL) and antibody building blocks have emerged as a strategy for the targeted treatment of cancer cells. Using a single-chain derivative of homotrimeric TRAIL (scTRAIL), several targeted and non-targeted scTRAIL fusion proteins of varying geometries and valencies for TRAIL receptors and target antigens, all comprising an Fc region, were generated. These fusion proteins comprised either 1 or 2 scTRAIL units, i.e. are tri- or hexavalent for TRAIL receptors and in the targeted versions, 1 or 2 binding sites for EGFR. These fusion proteins were analyzed for cell binding and cell death induction using the EGFR-expressing colorectal cancer cell lines Colo205 and HCT116. In line with previous findings, all fusion proteins that were hexavalent for TRAIL receptors exhibited a strongly increased cell killing activity compared to the trivalent ones. Interestingly, the fusion proteins comprising one scTRAIL unit, did not benefit from targeting to EGFR. In contrast, the hexavalent scTRAIL fusion proteins further benefited from EGFR targeting, resulting in an approximately 6- to 30-fold increase in cell killing. In summary, this study shed further light on the influence of geometry and valency of TRAIL fusion proteins and confirmed IgG-scTRAIL fusion proteins as highly potent cell death inducers.